Perbedaan Indeks Massa Tubuh pada Ibu Hamil Hipertensi dengan Normotensi - Netti Meilani Simanjuntak; Suci Nanda Resti; Friska Margareth (Prodi D III Kebidanan Fakultas Ilmu Kesehatan Universitas Ibrahimy, 2023)
Hypertension that occurs during pregnancy can cause pre-eclampisa and eclampsia. This situation can endanger the condition of the mother and fetus in the womb if it is not detected early. Many things influence the incidence of hypertension in this pregnancy, one of which is the body mass index (BMI). This study aims to determine differences in the body mass index of pregnant women who experience hypertension and normotension in working area of Puskesmas Hutapaung in 2022. This type of quantitative research was observational analytic with a cross sectional approach. This sample was taken using purposive sampling of 32 pregnant women who were divided into 2 groups. A total of 16 pregnant women with hypertension and 16 normotensive pregnant women. Data collection used an observation sheet which was analyzed using an indepent t-test. The results of this study showed that there are differences in the body mass index of hypertensive and normotensive pregnant women. It is expected that pregnant women need to check their body mass index and maintain a healthy diet.